DEVELOPMENT OF INTERACTIVE TEACHING MATERIALS FOR EXPLANATORY TEXT MATERIALS BASED ON LOCAL WISDOM CLASS IX at MTs AL-KAUTSAR PEKANBARU - Ahmad Wahyudi Suherman; Asnawi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to develop interactive teaching materials for explanatory text materials based on Riau Malay local wisdom with the help of the LUMI website for grade IX students of MTs Al-Kautsar Pekanbaru and test the level of validity, practicality, and effectiveness in learning Indonesian. This research uses the Research and Development (R&D) method with the ADDIE model which includes the analysis, design, development, implementation, and evaluation stages. The research subjects consisted of material experts, media experts, Indonesian language teachers, and grade IX students. Data collection techniques are carried out through observation, interviews, validation questionnaires, teacher and student response questionnaires, and learning outcome tests in the form of pretests and posttests. Data were analyzed using quantitative descriptive analysis and paired-sample t-test. The results of the study show that interactive teaching materials assisted by the LUMI website are in the category of very valid based on the assessment of material experts and media experts. The responses of teachers and students show that teaching materials are practical in learning because they have an attractive appearance, are easy to operate, and are able to increase student engagement. In addition, the results of the effectiveness test showed an increase in student learning outcomes after using interactive teaching materials with a significance value of < 0.05. The integration of Riau Malay local wisdom through Malay poems, poems, and Malay Tutoring makes learning more contextual and meaningful for students. Thus, interactive teaching materials based on Riau Malay local wisdom with the help of the LUMI website were declared feasible, practical, and effective for use in learning explanatory texts in grade IX MTs